2017
DOI: 10.1161/atvbaha.116.308682
|View full text |Cite
|
Sign up to set email alerts
|

Adam17 Deficiency Promotes Atherosclerosis by Enhanced TNFR2 Signaling in Mice

Abstract: Objective— ADAM17 (a disintegrin and metalloproteinase 17) is a sheddase releasing different types of membrane-bound proteins, including adhesion molecules, cytokines, and their receptors as well as inflammatory mediators. Because these substrates modulate important mechanisms of atherosclerosis, we hypothesized that ADAM17 might be involved in the pathogenesis of this frequent disease. Approach and Results— Because Adam17 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
45
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(49 citation statements)
references
References 61 publications
3
45
0
Order By: Relevance
“…Therefore, it was assumed that elevated levels of ADAM17 in the plaque would result in accumulation of apoptotic debris and expansion of atherosclerotic lesions. However, recently Nicolaou et al showed that in Ldlr−/− mice with a hypomorphic mutation that lowers ADAM17 expression, ADAM17-deficient cells had reduced apoptosis and atherosclerotic lesions from these mice had increased numbers of both macrophages and SMCs 17 . This was attributed to the increased signaling through TNF receptor 2 (TNFR2) and membrane-bound TNFα which promoted cell survival and pro-inflammatory signalling.…”
Section: The Goodmentioning
confidence: 99%
“…Therefore, it was assumed that elevated levels of ADAM17 in the plaque would result in accumulation of apoptotic debris and expansion of atherosclerotic lesions. However, recently Nicolaou et al showed that in Ldlr−/− mice with a hypomorphic mutation that lowers ADAM17 expression, ADAM17-deficient cells had reduced apoptosis and atherosclerotic lesions from these mice had increased numbers of both macrophages and SMCs 17 . This was attributed to the increased signaling through TNF receptor 2 (TNFR2) and membrane-bound TNFα which promoted cell survival and pro-inflammatory signalling.…”
Section: The Goodmentioning
confidence: 99%
“…It could be a protective mechanism preventing overstimulation from the continuous or repeated exposure to HMGB1. In line with it, ADAM17 was atheroprotective and its deficiency was shown to promote atherosclerosis in mouse models of atherosclerosis [31,32].…”
Section: Cellular Physiology and Biochemistry Cellular Physiology Andmentioning
confidence: 79%
“…Later they showed evidence that the atherosclerosis resistance of FVB.LDLR −/− mice could be explained by their increased TACE expression and activity (Holdt et al, ). The same group provided further evidence that TACE‐deficient LDLR −/− mice developed larger atherosclerotic lesions, which might be caused by the reduced shedding of TNF‐α and TNFR2 and resulted constitutive activation of TNFR2 signaling (Nicolaou et al, ). Therefore, TACE is likely a candidate gene of atherosclerosis susceptibility.…”
Section: Discussionmentioning
confidence: 97%
“…TACE is known to be responsible for the liberation of the inflammatory cytokine TNF‐α and its receptors, and also ligands of the epidermal growth factor receptor (EGFR), thus playing as an important switch in regulating cell proliferation, inflammation, and cancer progression (Scheller, Chalaris, Garbers, & Rose‐John, ). Holdt and his colleagues revealed in their works that the activity of TACE was closely related with the development of atherosclerosis (Holdt, Thiery, Breslow, & Teupser, ; Nicolaou et al, ). TACE was also proved to play an essential role in the post‐myocardial infarction repair by regulating angiogenesis (Fan et al, ).…”
Section: Introductionmentioning
confidence: 99%